Implementation evaluation model to measure virtual learning environment success factors among Malaysian teachers - Hapini, Awang (2019)
Despite the various benefits offered by Virtual Learning Environment (VLE), its usage among Malaysian teachers is still low, indicating that the system is not in the right track of success. Therefore, this study aims to develop a model to measure VLE success among Malaysian teachers based on the updated DeLone & McLean IS Success Model (D&M). This study employed an explanatory sequential mixed method design. Eight hundred and fifty (850) questionnaires were distributed to respondents across the northern region of Malaysia using simple random sampling procedure. The QR code was used to speed up the data collection without violating the rules of probability sampling. As a result, 719 questionnaires were returned and 643 are usable for the main analysis. The quantitative data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Most of hypothesized direct relationships are supported, except for Use to Intention to Use, which is fully mediated by User Satisfaction. The result also confirmed the positive moderating role of Workload. However, the moderating role of Personal Characteristics is not supported. Furthermore, the issue of recursive relationships, which produced two R² and Q² in certain endogenous variables, was investigated by comparing five possible models. Consequently, the produced model can be analyzed on a single structural model and therefore, provides valid predictive accuracy and relevance. This analysis has become a major methodological contribution of the study that provides a foundation for further investigations on the relevancy of the recursive relationships in D&M. Based on the final model, the VLE implementation strategy was produced and presented to 14 practitioners. Next, the validation was done using qualitative content analysis. The result indicates that the implementation strategy can be applied in Malaysian schools. Finally, this study contributes to the body of knowledge by providing a model to measure VLE success among teachers.